KARAKTERISTIK FISIK DAN KIMIA BUAH TOMAT HASIL PELAPISAN DENGAN PATI TALAS - Rusmanto, Eko; Rahim, Abdul; Hutomo, Gatot Siswo (AGROTEKBIS, 2017)
The tomato fruit is the klimaterik fruit easily broken after harvested. One of the post harvest handling technology that can be applied on tomato fruit, namely edible starch taro-based coating. This research aims to know the best taro starch concentration can be used as upholstery materials (edible coating) in the handling of post harvest of tomatoes based on its chemical and physical characteristics. This research was carried out in January to April 2016, in the Laboratory of Industrial agriculture, Faculty of Agriculture, University of Tadulako, Palu, Central Sulawesi. Research design used was complete randomized design (CRD). This research using the method of immersion (dipping) on tomato fruit coating by using 5 starch concentration of taro treatments are: 0, 1, 3, 5 and 7% and it repeated twice. The results showed that the concentrations of taro starch is best for coating edible materials (coatings) in post-harvest handling tomato fruit is of 1-3%. As for the physical characteristics of tomato fruit is relatively the same red color is determined visually and smoothly (0,31 mm -0,32/g/s), while the chemical characteristics of tomato fruit including moisture content (93,32-94,61%), vitamin C (10,12-11,30 mg/100 g), sugar levels (1,51-1,54%) and respiratory rate (0,24-0,29 mg CO2/kg/hour).Â Keywords : Edible Coating, Taro Starch, Tomatoes.